The Relationship between Anxiety Levels and Pain Degrees in Postoperative Caesarean Patients at Pasirian Hospital - Zainal Abidin; Rizka Yunita; Sharifah Aini Tika Rachmad (KHD-Production, 2022)
Surgery is a potential or actual threat to a person's integrity that can arouse anxiety when faced with it, thus causing feelings of discomfort or fear. One of the most common responses in postoperative patients is the level of anxiety and discomfort. This study aims to analyze the relationship between the level of anxiety and the degree of pain in postoperative sectio caesarea patients at Pasirian Hospital. This research is a correlational study with a cross sectional research design. Data were taken from postoperative sectio caesarea patients with SAB anesthesia at Pasirian Hospital with the instruments used were anxiety level questionnaire sheets (HARS) and pain level observation sheets. The total population of 45 respondents, the sample studied was 40 respondents by accidental sampling. Then the data were analyzed manually and on a computer with the Spearmank Rank test. The results showed that of the 40 respondents studied, most (52.5%) aged 31-40 years, education level (70%) had high school education, based on occupation (57.5%) Housewives (IRT), (67.5 %) did not have a history of cesarean section, (52.5%) were primigravida in the history of labor, and primigravida (52.5%) had a history of distance delivery. Meanwhile (70%) respondents with the characteristics of severe anxiety levels and the characteristics of severe pain degrees were (60%) respondents. Based on the Spearmank Rank test, the p value of 0.000 is smaller than (0.05), it can be concluded that H1 is accepted, meaning that there is a relationship between the level of anxiety and the degree of pain in postoperative cesarean section patients at Pasirian Hospital. Pain is everyone's subjective, so as a nurse must assess and evaluate the problem of pain. Provide information about the surgical process and provide relaxation therapy to patients to reduce anxiety levels.